WATER QUALITY IN BANDENG FISH POUNDS IN LAMDINGIN VILLAGE BANDA ACEH - Ulpha, Ramadhani Andrawina; Fianti, Fianti; Yulianti, Ian (Physics Communication, 2021)
The people in Lamdingin village rely on aquaculture activities as their livelihood. The commodities cultivated in the pond are milkfish, tilapia, and shrimp. Water quality conditions have a significant role in the success of fish farming. Water as a living habitat for cultivated fish must be in optimal conditions in terms of quantity and quality. Therefore, water quality is the important factor in fish farming. This study aims to determine water quality based on parameters of brightness, temperature, salinity, and pH in milkfish ponds in Lamdingin village. Sampling and measurement were carried out at 09.00 in the morning for one week. Brightness was measured using a Secci disk, the temperature was measured using a digital thermometer, salinity was measured using digital salinity, and pH was measured using a pH meter. The results showed that the brightness, temperature, salinity and pH were 27.42 cm, 28.5 0C, 30.25 ppt and 7.42, recpectively. These results meet the Indonesian National Standard (SNI).